Analisis Efektivitas Intensifikasi Pajak Bumi Dan Bangunan Perdesaan Dan Perkotaan Dalam Meningkatkan Pendapatan Asli Daerah Kota Jakarta Timur Pada Masa Pandemi Covid-19 - Angghitya Alfantica Sofiat Wibowo; Khairur Razikin (Jurnal Ilmu Administrasi Publik, 2022)
The purpose of this study was to analyze the effectiveness of the implementation of the Rural and Urban Land and Building Tax intensification, the obstacles, and the efforts to increase Regional original revenue in East Jakarta during the Covid-19 pandemic. The phenomenon in this study is the lack of income due to the Covid-19 pandemic, it is considered as an obstacle that must be evaluated by the local government. Another problem is the lack of public knowledge or public awareness in fulfilling the obligation to pay the tax. Thus, the government needs to implement tax intensification to increase tax collection. The research method used was qualitative with a descriptive research type. The results of this study indicated that the Rural and Urban Land Tax intensification activities carried out during the Covid-19 Pandemic for the 2019-2020 period went well. Although, nominally, the targets that have been set were not in accordance with the realization of the achievements. However, in percentage, the implementation is categorized as effective. The obstacle that occurs is the lack of public awareness in carrying out their obligations. The effort made is in the form of providing socialization or counseling to taxpayers.